A global model study of low pressure high density CF4 discharge. (25th February 2019) - Toneli, D A; Pessoa, R S; Roberto, M; Gudmundsson, J T
Abstract: We present a revised reaction set for low pressure high density CF4 plasma modelling. A global model (volume averaged) was developed to study a CF4 discharge that includes the neutral species CF4, CF3, CF2, CF, F2, F, and C, the metastable states CF(a 4 Σ − ) and CF2 ( 3 B1 ), the positive ions CF 3 +, CF 2 +, CF +, F 2 +, F +, and C +, the negative ions CF 3 −, F 2 −, and F −, and electrons. The main reactions that contribute to the production and loss of each species are pointed out with an emphasis on the radicals CF2, CF and F, the dominant positive ion CF 3 +, and the dominant negative ion F − . We find wall processes to have a significant influence on the discharge. The density of F2 is high due to recombination of F atoms at the walls and the losses of the radicals F, CF, and CF3 are mainly through wall recombination. As the pressure is increased, F − becomes the dominant negative charged species. The discharge is found to be weakly electronegative below ∼10 mTorr and the electronegativity decreases with increased absorbed power.